Pengaruh LKPM Terhadap Kemajuan NIB Diera Digitalisasi - Wibi Azhar Firmansyach AK; Endang Indartuti (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The provision of public services to the community is one of the most important tasks of government. In order to fulfill the needs and interests of the community, public services are provided by the government, private parties acting on behalf of the government, or private parties directly to the community, whether financed or unfinanced. Strategic roles and functions in the field of implementing integrated licensing services in Surabaya City are carried out by the Surabaya City Investment and One-Stop Integrated Service Office (DPMPTSP). This office was formed based on Surabaya Mayor Regulation Number 084 of 2021 concerning the Position, Organizational Structure, Job Description, and Functions and Work Procedures of the Investment and One-Stop Integrated Service Office of Surabaya City. The program carried out by these students aims to increase productivity and efficiency in public services. With this, the expected results are good in terms of productivity, effectiveness and efficiency.